Substantiation of the choice tactics for the treatment of multiple and associated fractures of long bones, depending on the injury severity and victims condition - Лапшин, Дмитро Вячеславович (ScienceRise: Medical Science, 2016)
The aim of the article is substantiation of the optimal tactics and volume of osteosynthesis of patients with multiple and combined fractures of the long bones, which polytrauma severity was 25–40 points according to ISS scale and condition severity according to MFS-IC, added with age indices, 21–32 points. Methods. The clinical base of research included 104 patients of this category, divided in 2 groups by the sign of one-stage (main) or two-stage (group of comparison) operative treatment. The system of objective medical and social criteria of treatment efficacy, offered by the authors, allowed rather reliably determine the optimal character, volume and terms of operative interventions. Results. The terms of main stages of fractures consolidation in patents with two-stage technique of osteosynthesis exceeded the analogous ones in patients with one-stage technique in 1,3–1,6 times; the severity of complications in patients, who underwent the two-stage treatment of multiple and combined fracture of the long bones were more than in victims with analogous traumas, who underwent the one-stage technique of osteoporosis; the terms of staying on the stationary treatment of patients, who underwent the one-stage treatment were 1,7times less than in ones, who underwent the two-state tactics of osteosynthesis; the mean terms of fractures consolidations in patients, who underwent the one-stage surgical treatment were 1,3–1,4 less by the all types of fractures and their combinations than in patients, who underwent the two-stage surgical treatment. Conclusions. The one-stage realization of the all types of extrafocal and closed intramedullary blocking osteosynthesis is optimal for this category of patients